Analisis Faktor-Faktor yang Mempengaruhi Ekspor Produk Olahan Kayu di Kabupaten Gianyar - Gayatri, Luh Ketut Prami; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 1, Januari 2016 (pp. 1 - 215), 2016)
Indonesia is one of the developing countries, which can not be separated from international trade one of which is exported. Gianyar Regency is one of the areas which also exports, one commodity is processed wood products. This study aims first to analyze and determine the effect of exchange rate US dollars, the amount of production and the rate of inflation on the export of wood products Gianyar regency simultaneously and partially, as well as to analyze and determine which variables are the dominant influence on the export of wood products in Gianyar . The data used in this research is secondary data and the data obtained from the relevant agencies namely the Department of Industry and Trade Gianyar regency as well as Bank Indonesia. Then the data is processed by multiple regression analysis techniques that were previously equipped with the classical assumption. The test results with SPSS 17.0 to obtain the results of the US dollar exchange rate, the amount of production and the rate of inflation simultaneously significant effect on the export of wood products in Gianyar. Partially US dollar exchange rate had no significant effect on the export of wood products in Gianyar, total production of positive and significant impact on the export of wood products in Gianyar, the inflation rate had no significant effect on the export of wood products in Gianyar. Production quantities are variables the dominant influence on the export of wood products in Gianyar.
Keywords: export; US dollar Exchange Rate; the amount of productions; inflation